STUDI ASPEK SOSISAL EKONOMI MASYARAKAT SEKITAR KAWASAN INDUSTRI DI KABUPATEN SIAK, RIAU - Almasdi Syahza; Shorea Khaswarina (Universitas Riau, 2002)
Siak Regency is area for development ofmining industries. The objective of this researchis to asses the impact of industrial development on social and economic status of peopleliving around tliis industrial area, namely: population, income distribution, education, socialinstitutions, busines.s opportunities, and the companies attitudes toward people around theindustrial area. Data and information area collected through a survey by purposive sam-pling. The research results show that the development of industrial area in Siak has a sig-nificant impact on social and economic progress in the area, such as business opportunities,employment, and income distribution. The development has also created new centers ofeconomic growth, local markets and local transportation facilities. From observation, it isfound that companies in the area haenough atfcnlion toward local people by providingthem working capital for small business, practical skills, education, clinic and other socialfacilities.